please solve this question(prove it)
Attachments:
![](https://hi-static.z-dn.net/files/d0b/1370b353af4c7b22549f776e9992c6d0.jpg)
Answers
Answered by
4
Step-by-step explanation:
LHS = cot^2A - cot^2B
= cosec^2A - 1 - cosec^2B + 1 (Identity: cot^2Ф = cosec^2Ф - 1)
= cosec^2A - cosec^2B
RHS = cosec^2A - cosec^2B
Hence Proved
Answered by
1
Answer:
not now
i will give you in next question iam
Similar questions
Math,
6 months ago
Social Sciences,
6 months ago
Social Sciences,
6 months ago
Math,
1 year ago
English,
1 year ago
Physics,
1 year ago